The Influence of Different Management Modes on the Potential of Moso Bamboo Carbon Sink Based on Survey Data of Yuhang and Lin’an - Shiyun Zhang; Irfan Mir Chohan; Ye Deng (International Journal of Engineering and Management Research, 2021)
Bamboo forest carbon sequestration has strong development potential in coping with global climate change. The management of Moso bamboo forest can exert its own strong carbon sequestration ability and promote farmers' income, which is the fundamental point of bamboo industry development and can integrate ecological, economic, and social benefits. In this study, two Moso bamboo forests with different management modes in Lin'an and Yuhang of Zhejiang Province were used as research points. Using the system dynamic thinking method, a dynamic system model was constructed to simulate the growth process of Moso bamboo and its carbon sink supply. Then comparative analysis was made of its carbon sink supply potential. It is easy for bamboo forest managers to change management measures according to their requirements and create a dynamic balance between ecology and economics when determining the optimum management mode for the bamboo forest under the supply potential of carbon sink. According to the study results, the carbon sink supply under the intensive model is the most ideal, while the carbon sink supply under the extensive peach blossom model is the least ideal.